(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the history of gold mining in the Emirate of Bukhara. It is also analyzed based on archival data and sources. The main attention is focused on the expeditions and mining works carried out by Russian researchers. It is also clear that the issuance of the decision "On gold mining" has created a number of opportunities in the territory of the country. As a result of the issuance of the decree "On gold mining", interest in the territory of the emirate to conduct many research works begins. In particular, the activity of Juravko-Pokorsky accelerates the process of gold mining. In this article, the main goal is to analyze mining issues of Bukhara Emirate based on sources, to study the progress of mining operations.